TERAPIA COGNITIVO-COMPORTAMENTAL COM CASAIS COMBINADA COM MINDFULNESS: INVESTIGAÇÃO DOS EFEITOS DA INTERVENÇÃO E DA ATENÇÃO CONSCIENTE NO FUNCIONAMENTO DIÁDICO - Duraes, Ricardo Silva dos Santos (2021)
Psychosocial factors permeate marital conflicts and might lead to divorce, in addition to being a risk for psychiatric disorders among spouses. Associated to this are psychological, cognitive, and emotional variables. The aim of this study was to verify the effects of the intervention and awareness attention on dyadic functioning. The instruments used in order to measure and obtain these data were Revised NEO Five-Factor Inventory (NEO-FFI-R), Marital Social Skills Inventory (IHSC); Revised - Dyadic Adjustment Scale (R-DAS), Mindful Attention Awareness Scale (MAAS), Beck Depression Inventory (BDI-II) and Sociodemographic Questionnaire. The sample was composed of 34 heterosexual participants (17 couples), 9 from the control group (CG) and 8 from the experimental group (EG), with minimum of one year married, Brazilians, minimum of 18 years and maximum of 60 years old, without any serious clinical psychological disorder and not drug addict. In the procedure, all couples completed the aforementioned instruments, before and after the intervention and at the 3-month follow-up, except NEO-FFI-R, which only was completed before of randomized phase. GE couples went through eight cognitive-behavioral 1hr20 sessions weekly and daily Mindfulness practices. GC participants went through four 1hr30 lectures after finishing the study. Results: This study showed effectiveness in the intervention for couples in conflicts and communication deficits, in marital relationship between 1 and 17 years, low income and education, and for all personality traits, except for Conscientiousness that was not evaluated in the EG. The significance effect results of the therapy on variables measured over time (pre-, post- and follow-up) were R-DAS (p = 0.001), MAAS (p = 0.001), IHSC (p = 0.009) and BDI-II (p = 0.000). Regarding the effect of sociodemographic variables on aware attention, the main effect of MAAS was significant for sex (p = 0.007), time of marital status (p = 0.006), education (p = 0.000), income (p = 0.009) and also for the variable personality traits (p = 0.010). Conclusion: The findings of this study suggest that CBCT combined with Mindfulness practices is effective in treating poorly educated and less financially favored couples. In addition, Mindfulness practices have shown positive results in improving executive attention, contributing to successful communication training and problem solving, reducing marital conflicts, and reducing levels of depressive symptoms. This study also showed some characteristics and tendency of behavior among couples in conflicts and how to manage the intervention. Finally, the intervention protocol might serve as prophylactic and health promotion measures for couples.